Pemahaman Intertekstual dalam Kitab Pengkhotbah - Studi Terjemahan Bahasa Inggris oleh Mahasiswa Teologi dan Pendapat Masyarakat - Marudut Bernadtua Simanjuntak (Universitas Maritim AMNI Semarang, 2023)
This study aims to investigate the intertextual understanding of Ecclesiastes in English by theology students and the opinions of the general public. The main focus of this research is to understand how students can read and understand the Bible, especially the Book of Ecclesiastes, in English. In addition, this study also seeks to explain how students and the community can form active communication and discussions regarding intertextual understanding. In addition, this research aims to explore how Christians in Jakarta, especially in suburban areas such as Bekasi, Depok, Tangerang, and Bogor, view the presence of Christian theology students in contributing to society. The research method used in this study involved opinion surveys and interviews with theology students and the general public. Theology students will be asked to read and understand the book of Ecclesiastes in English translation, while their opinions and responses will be collected through surveys and interviews. Opinions from the general public will be collected through a survey which will be disseminated in various areas of Jakarta, especially in the suburbs. The collected data will be analyzed qualitatively to identify the main patterns and findings in intertextual understanding and perceptions of the contribution of Christian theology students in society. This research is expected to provide practical benefits in increasing understanding of the Bible in English, especially the Book of Ecclesiastes, as well as strengthening active communication and discussion in intertextual understanding. In addition, the results of this study can strengthen the relationship between Christian theology students and the community, especially in the Jakarta area, by demonstrating their contribution to service and positive contributions to society.